Using telemedicine to improve access, cost and quality of secondary care for people in prison in England: a hybrid type 2 implementation effectiveness study. Issue 2 (18th February 2020) - Edge, Chantal; George, Julie; Black, Georgia; Gallagher, Michelle; Ala, Aftab; Patel, Shamir; Edwards, Simon; Hayward, Andrew
Abstract : Introduction: People in prison tend to experience poorer health, access to healthcare services and health outcomes than the general population. Use of video consultations (telemedicine) has been proven effective at improving the access, cost and quality of secondary care for prisoners in the USA and Australia. Implementation and use in English prison settings has been limited to date despite political drivers for change. We plan to research the implementation of a new prison-hospital telemedicine model in an English county to understand what factors drive or hinder implementation and whether the model can improve healthcare outcomes as demonstrated in other contextual settings. Methods and analysis: We will undertake a hybrid type 2 implementation effectiveness study to gather evidence on both clinical and implementation outcomes. Data collection will be guided by the theoretical constructs of Normalisation Process Theory. We will prospectively collect data through: (1) prisoner/patient focus groups, interviews and questionnaires, (2) prison healthcare, hospital and wider prison staff interviews and questionnaires, (3) routine quality improvement and service evaluation data. Up to four prisons and three hospital settings in Surrey (England) will be included in the telemedicine research, dependent on their telemedicine readiness during the study period. Prisons proposed include male and female prisoners, remand (not yet sentenced) and sentenced individuals and different security categorisations. In addition, focus groups in five telemedicine naïve prisons will provide information on patient preconceptions and concerns surrounding telemedicine. Ethics and dissemination: This study has received National Health Service Research Ethics Committee, Her Majesty's Prison and Probation Service National Research Committee and Health Research Authority approval. Dissemination of results will take place through peer-reviewed journals, conferences and existing health and justice networks.